Effect of Tdap upon antibody response to meningococcal polysaccharide when administered before, with or after the quadrivalent meningococcal TT-conjugate vaccine (coadministered with the 13-valent pneumococcal CRM197-conjugate vaccine) in adult Hajj pilgrims: A randomised controlled trial. Issue 29 (5th July 2018) - Tashani, M.; Alfelali, M.; Barasheed, O.; Alqahtani, A.S.; Heron, L.; Wong, M.; Rashid, H.; Findlow, H.; Borrow, R.; Booy, R.
Abstract: Hajj pilgrims are susceptible to several serious infections and are required to receive multiple vaccinations. Polysaccharide-protein conjugate vaccines contain carrier proteins such as tetanus toxoid (TT), diphtheria toxoid or a mutant of diphtheria toxoid (CRM197). These carrier proteins may interact with other conjugate or combination vaccines containing tetanus or diphtheria on concurrent or sequential administration. We examined the immune interaction of separate and concomitant administration of a tetanus/diphtheria/acellular pertussis (Tdap) vaccine with a TT-conjugated quadrivalent meningococcal vaccine (MCV4) (coadministered with 13-valent pneumococcal CRM197-conjugate vaccine [PCV13]) in adult Australian pilgrims before attending Hajj in 2015. We randomly assigned each participant to one of three vaccination schedules. Group 1 received Tdap 3–4 weeks before receiving MCV4 coadministered with PCV13. Group 2 received all three vaccines concomitantly. Group 3 received MCV4 and PCV13 3–4 weeks before Tdap. Blood samples were collected at baseline, at each vaccination visit and 3–4 weeks after vaccination and tested for response to meningococcal serogroups C, W and Y using a serum bactericidal antibody (rSBA) assay with baby rabbit complement, and to diphtheria and tetanus toxoid, measuring IgG antibodies by ELISA. Participants completed symptom diaries after each vaccination. A total of 166 participants aged 18–64 (median 42) years were recruited, of whom 160 completed the study. Compared to the other groups, Group 1 (given Tdap first) had significantly lower proportion of subjects achieving a ≥4-fold rise in rSBA for serogroup W. No difference was detected across the three groups in achieving protection threshold (rSBA ≥8 post vaccination) or SBA geometric mean titre (GMT) post vaccination. Group 3, which was given MCV4/PCV13 first, had high levels of antibody against diphtheria and tetanus than the other groups, when tested prior to receipt of Tdap; Only the anti-tetanus responses remained significantly higher after Tdap administration. No serious adverse events were reported. In conclusion, when multiple vaccination is required for Hajj pilgrims, administering Tdap concurrently with MCV4/PCV13 produces adequate immune responses, and avoids meningococcal immune interference, in the convenience of a single consultation. However, giving Tdap 3–4 weeks after MCV4/PCV13 has the advantage of an enhanced tetanus toxoid response. The trial is Trials Registry (ANZCTR): ACTRN12613000536763.